Reasoning in chemistry teacher education - Khan Samia (Chemistry Teacher International, 2024)
Research on preservice science teacher’s reasoning is comparatively new in a larger field of research on reasoning. This study examines model-based reasoning among preservice science teachers to make recommendations on how reasoning can be fostered within chemistry teacher education. It coalesces over 20 years of a program of research in this area. Firstly, several empirical studies on undergraduate students and their reasoning are examined. Future chemistry teachers are drawn from this pool of undergraduate students. Secondly, empirical studies in preservice teacher education are examined to highlight reasoning among preservice chemistry teachers. Thirdly, recommendations are put forward for future research on the development of scientific reasoning among chemistry teachers as an important facet of chemistry teacher education.